The downsized veggie garden : how to garden small wherever you live, whatever your space - Copsey, Kate (St. Lynn's Press, 2016)
Small is beautiful, and integrating a small, easy-to-manage garden into hectic everyday life is easy. In The Downsized Veggie Garden, low maintenance is the mantra. And so is making smart, creative use of the space we have -- whether it's outdoors, indoors, in-ground, in containers, on a balcony railing...or even going vertical. Garden expert Kate Copsey takes the reader season-by-season, plant-by-plant, with essential tips about soil, seed-starting, plant choices, non-chemical fertilizing, watering, choosing the right containers, veggie garden planning and planting, and much more. This fully illustrated book is a one-stop guide for the beginner gardener or the downsizing gardener.